Exploring Gene Expression and Alternative Splicing in Duck Embryonic Myoblasts via Full-Length Transcriptome Sequencing - Jintao Wu; Shuibing Liu; Dongcheng Jiang; Ya’nan Zhou; Hongxia Jiang; Xiaoyun Xiao; Boqian Zha; Yukai Fang; Jie Huang; Xiaolong Hu; Huirong Mao; Sanfeng Liu; et al. (Veterinary Sciences)
The duck industry is vital for supplying high-quality protein, making research into the development of duck skeletal muscle critical for improving meat and egg production. In this study, we leveraged Oxford Nanopore Technologies (ONT) sequencing to perform full-length transcriptome sequencing of myoblasts harvested from the leg muscles of duck embryos at embryonic day 13 (E13), specifically examining both the proliferative (GM) and differentiation (DM) phases. Our analysis identified a total of 5797 novel transcripts along with 2332 long non-coding RNAs (lncRNAs), revealing substantial changes in gene expression linked to muscle development. We detected 3653 differentially expressed genes and 2246 instances of alternative splicing, with key genes involved in essential pathways, such as ECM–receptor interaction and Notch signaling, prominently featured. Additionally, we constructed a protein–protein interaction network that highlighted critical regulators—MYOM3, MYL2, MYL1, TNNI2, and ACTN2—associated with the processes of proliferation and differentiation in myoblasts. This extensive transcriptomic investigation not only sheds light on the intricate molecular mechanisms driving skeletal muscle development in ducks but also provides significant insights for future breeding strategies aimed at enhancing the efficiency of duck production. The results emphasize the efficacy of ONT sequencing in uncovering complex regulatory networks within avian species, ultimately contributing to progress in animal husbandry.